Disadvantages of Linguistic Origin – Evidence from Immigrant Literacy Scores - Ingo Isphording (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
This study quantifies the disadvantage in the formation of literacy skills of immigrants that arises from the linguistic distance between mother tongue and host country language. Combining unique cross-country data on literacy scores with information on the linguistic distance between languages, gaps in literacy test scores are estimated. Linguistically distant immigrants face significant initial disadvantages of linguistic origin that exceed existing differentials across wage distributions and between employed and unemployed subpopulations. The importance of the linguistic origin increases with the age at migration, confirming the linguistic Critical Period hypothesis. Assimilation in literacy scores is moderate and does not offset the initial disadvantage. – – Diese Studie befasst sich mit der Quantifizierung von Nachteilen im Spracherwerb von Immigranten, die auf die linguistische Distanz zwischen Muttersprache und Sprache des Gastlandes zurückzuführen sind. Als Datenbasis dient die International Adult Literacy Study, welche mit linguistischer Information über die Unterschiedlichkeit von Sprachen angereichert wird. Die Ergebnisse weisen auf deutliche Anfangsschwierigkeiten im Spracherwerb aufgrund höherer linguistischer Distanz hin. Ein weiterer Fokus liegt auf der Überprüfung der Hypothese der kritischen Periode, die einen nahezu mühelosen Spracherwerb bis zur Adoleszenz vorhersagt. Der steigende Einfluss der linguistischen Distanz mit steigendem Alter bei Migration unterstützt diese Hypothese.
Keywords: F22; J15; J24; J31; 330; linguistic distance; literacy; human capital; immigrants